Laser controlled melting of H12 hot-work tool steel with B4C particles at the surface. (November 2015) - Yilbas, B.S.; Patel, F.; Karatas, C.
Abstract: Laser controlled melting of pre-prepared H12 hot-work tool steel surface is carried out. B4 C particles in the carbon film are located at the workpiece surface prior to the laser treatment process. Nitrogen at high pressure is used as an assisting gas during the laser melting. Morphological and metallurgical changes in the treated layer are examined using scanning electron microscope, energy dispersive spectroscopy, and X-ray diffraction. Microhardness of the treated surface is measured and the residual stress formed at the treated surface vicinity is obtained using the X-ray diffraction technique. It is found that a dense layer consisting of fine grains is formed at the treated surface. Microhardness of the treated surface improves significantly because of fine grains, nitride compounds formed at the surface and micro-stresses developed due to mismatched of thermal expansion coefficients of B4 C and the base material. The residual stress formed at the surface is suppressed by the self annealing effect of the initially formed laser scans. Highlights: No micro-crack is observed in close region of B4 C particles. Nitrogen diffusion results in the formation of γ'-Fe4 N compound below surface. Fe3 (C, N) is formed at the surface. Microhardness increases notably after treatment. Laser treatment reduces friction coefficient of the surface.